(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Wireless security can be defined as the inhibition of unlawful access or intrusion of devices operated on wireless networks. The global community has witnessed a rapid increment in the distribution of wireless networks due to the rigorous advancement in technology that calls for the intensive use of wireless network systems. Wireless networks are broadly clustered into four major categories, namely, Wireless personal area network (WPAN), wireless Local Area Network (WLAN), Wireless Metropolitan area network (WMAN), and Wireless wide area network (WWAN). The wireless network system is distinct from the contemporary wired system in that communication through this medium is through electromagnetic radiation, not wires, as is the case with wired networks. The nature of the wireless networks makes them more susceptible to threats, and their unique transmission system makes securing the network quite intricate. Although a wireless network comes with enhanced flexibility and portability and a reduced budget for the users, its security features need to be improved to cushion its users from potential threats. This paper focuses on assessing existing and new threats, possible areas of vulnerability in the wireless network system, and probable solutions to curb the threats.